ANALISIS PENERAPAN WITHHOLDING TAX SYSTEM PRESPEKTIF MUTATIS MUTANDIS PADA LEMBAGA KEUANGAN SYARIAH (Studi Kasus pada BMT Al-Hijrah KAN Jabung) - Kurniawati, Siti Eli (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
The research objective is to know the tax cut by sharia financial institution by referring to the Tax Legislation on Income Tax (PPh) that is generally applicable, as well as the procedures of tax cuts using the means of Withholding Tax System and the basic of tax imposition on revenue sharing in sharia financial institution.The data analyzing method used by the researcher is qualitative data analysis with Case Study formulate theory, looking at theory as well as cases as the induction process from the observation toward facts (gathering information). Based on the data analysis and interview result done in this research, the finding suggests that BMT Al Hijrah KAN Jabung have implemented tax system in accordance with the generally applicable tax provision as well as withholding tax system in BMT Al Hijrah KAN Jabung which is implemented in deposit revenue sharing and time mudharabah (deposito).